Formal Aesthetics of Poems for Indonesian Children Written by Adult Poets - Mulyono, Tri; Sayuti, Suminto A; Rustono, Rustono (Universitas Negeri Semarang, 2018)
This article discusses the formal aesthetics of poetry for Indonesian children. It was written based on a study conducted on 20 poems. The purpose of this study is to explain the formal aesthetics of the poems, which includes word, line, and discourse aesthetics. Data were drawn by reading and writing techniques. The data were then analyzed qualitatively. The framework was based on the theory of poetry for Indonesian children. The validity of the study was tested with semantic and intra-rater means. The results show that the formal aesthetics of the poems were found in the aspects of words, sentences or lines, and discourse. In the word aspect, the formal aesthetics was created by means of Javanese, Arabic (foreign), and synonymous vocabulary. In the aspect of sentence or line, the formal aesthetics was created through a means of question, inversion, and long as well as short sentences. In the aspect of discourse, the formal aesthetics was created by means of typography, linkage, enjambement, and homology. It was concluded that the aesthetic form of poems for Indonesian children which were written by adult poets is found in the aspects of words, lines or sentences, and discourse.